Proposta de caderno suplementar para o ensino das relações semânticas de antonímia e sinonímia em turmas de sexto ano - Ferreira, Cleidiana Cardoso Nazareno (2018)
The discursive competence versatility involves subjects that pass over promotive actions of the contextualized study of the lexicon. For that matter, the aim of this work was to offer a theoretical and practical subsidy for the Portuguese Language teacher, by means of drafts from vocabulary activities, related to the antonyms and synonyms, supplemental to the textbooks, bearing in mind the low occurrence of exercises from that nature in didactic material of wide distribution in Brazilian public schools. Thus, we believe that the teaching of the antonym and synonymy semantic relationships, in sixth degree groups, could contribute to the paths of the students' vocabulary expansion, aiding them in the development of a larger safety and lexical diversity in the discursive interactions. For us to reach our purpose, we went through the basic theoretical field of the Lexicology and its semantic bias, Lexicography and their directions for the teaching, vocabulary teaching and semantic and lexical relationships of antonym and synonymy. The base of that theoretical outlook was ruled in studies of Picoche (1977), Pottier (1978), Barbosa (1998; 2001), Biderman (2001; 2003), Dias (2004), Krieger (2011), Ilari (1985; 1997), among other studious. In those terms, our research was developed with participation of sixth degree students' from a public school of Distrito Federal (Federal District). Starting from the appreciation of the theoretical construct, descriptions and analyses of exercises on antonym and synonymy, which are present in the selected textbook, we produced activities addressed to the teaching of those semantic relationships. With that production, we began the application of the proposals in the sixth degree group, evaluating its viability. After the description and analysis of those intervention classes, it was possible to elaborate the Supplemental Notebook, with theoretical and practical suggestions of vocabulary activities on antonyms and synonymous, so that they contribute as suggestions to be relaxed by the teachers, in agreement with their work reality.